Balloon Pulmonary Angioplasty in Patients With Inoperable or Recurrent/Residual Chronic Thromboembolic Pulmonary Hypertension: A Single-Centre Initial Experience - YILDIZELİ, BEDRETTİN; KOCAKAYA, DERYA (My University, 2021)
Background Methods Results Conclusions
Balloon Pulmonary Angioplasty in Patients With Inoperable or Recurrent/Residual Chronic Thromboembolic Pulmonary Hypertension